Recombination of Hydrogen and Oxygen in Fluidized Bed Reactor with Different Gas Distributors - Ge, Sang; Xinchun, Lai; Weizhong, Qian; Wei, Cao; Congyu, Sheng; Yongjun, Su; Xiaoqiu, Ye (Energy procedia, 2012)
The recombination of hydrogen and oxygen with molar ratio of 2:1 and flow rate of 2 Nm3/h has been investigated in the fluidized bed reactor. It has been observed that the quick mixing of hydrogen and oxygen in Pt/Al2O3 catalyst is free of explosion and allows the effective recombination at the temperature of 373-873K. However, this highly exothermic reaction brings the much high temperature gradient result in the fluidized bed. And the hot spot in reactor is sometimes higher than 1173K, causing the rapid deactivation of the catalyst and lead to the dangerous explosion. As adopting the multistage gas distributor, the concentration of hydrogen in the pristine gas distributor region (always in the bottom of the reactor) is effectively reduced and the temperature in the catalyst dense phase can be controlled to 673-873K, allowing a stable and effective conversion of hydrogen up to 99.9997%. The present work provides a novel fluidization technology for the recombination of hydrogen and oxygen with high concentrations.